Performance analysis of React v. 18.1.0 and Angular v. 11.0.2 development frameworks - Albert Poniedziałek; Beata Pańczyk (Journal of Computer Sciences Institute)
This paper presents the results of the comparative analysis of the two JavaScript frameworks. The research was carried out using test applications with the same functionalities, implemented in both environments. The number of bytes occupied by both projects, the number of lines of code, the average RAM consumption and the time efficiency were used as criteria for comparison. Automatic load tests and technical analysis of both environments were performed. The results showed that React is able to better handle a large amount of data (around 100 000 records), while for small data sets oscillating around 1000 records, no significant differences in both application performance were demonstrated. For a medium number of records (10000), React proved to be more efficient.